Analysis of Grain Morphology, Mineral Composition, and Ore Grade on Gold Placer Deposits in Bantimurung, Pangkep Regency, South Sulawesi, Indonesia - Ulva Ria Irfan; Angga Alamin Husain; Irzal Nur (Journal of Geoscience, Engineering, Environment, and Technology, 2022)
The information through social media shows that there is quite an intense placer mining activity by local residents in the Bantimurung area, Tondong Tallasa District, Pangkep Regency. This study as a preliminary research aims to determine the grain morphology characteristics of mineral composition and metal grade in gold placer deposits in the study area. The data collected were eight samples. The collected samples were prepared into thin section, polished and observed using a microscope to identify the mineral composition and grain morphology. The grades of Au metal and its associated metals consisting of Ag, Zn, Pb, and Cu in the placer samples were analyzed by the AAS method. Petrography shows abundant of quartz, plagioclase, biotite and pyroxene minerals it might be indication of mineralization of epithermal. Ore petrography shows pyrite present along the river, silver is also found quite a lot along the river. Meanwhile, covellite, magnetite, sphalerite, and garnet were found only slightly at the sampling station this mineral composition indicates that the source of the placer deposits was epithermal. The grain morphology of the thin-section observation shows that quartz dominant has a high sphericity with character of roundness tends to be very angular to sub-rounded from upstream to downstream of the river. Plagioclase tends to have sub rounded roundness and high sphericity. Biotite tends to have a high sphericity with roundness from upstream to downstream is very angular, then angular, then sub-rounded. Pyroxenes tend to have high sphericity with very angular and angular roundness. Au content is directly proportional to Cu and inversely proportional to Zn, Pb, and Ag. Statistically Au affects the content of Cu by 50.97%. It can be concluded that Au is genetically associated with Cu, however Au grains that were still attached to the mineral and had not been separated from other minerals so that it could not be seen visually. This can also indicate that the source of this placer deposit is not far from the study site. Au grade corelated with stream sediment types it is 97,86 ppm for channel bar and 94,16 ppm for point bar, based on this we conclude the downstream has higher grade of Au compare to the upstream.